Implementation Of Online Passport Making Policy In Creating Good Governance At Tpi Cirebon Class I Immigration Office - Insan Kholis; Awaludin Putra Hertiansyah; Hery Nariyah; Moh. Sutarjo (International Journal Labs, 2024)
E-Passport has not achieved its goal of making passport services faster, clearer and more accountable since its launch as a public service. As a result, people have to come back repeatedly to get access to the app. This study investigates the use of e-government at the TPI Cirebon Class I Immigration Office. The aim is to find out how to use